Awareness among Intern Doctors Regarding Privacy and Confidentiality in Medical Practice (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Privacy and confidentiality in medical care are deeply rooted in core professional ethicalstandards across a variety of health professions. Present project aimed to study perceptions of intern doctorsregarding privacy and confidentiality in medical practice.Materials and methods: Total 100 intern doctors of GMERS Medical College, Valsad, Gujarat weresubjected to pre-tested and pre-validated Likert scale type questionnaire regarding knowledge and awarenessof privacy and confidentiality in medical practice after obtaining their informed written consent. Dataobtained were analyzed via median score and tabulated.Results: Out of 100 respondents, 58 were male and 42 were female. Knowledge and awareness regardingmany of the facts related to privacy and confidentiality of medical practice found to be satisfactorily withmedian score of more than 3. Professional secrecy is implied term of contract between doctor and patient,patient can sue the doctor for damages if disclosure is done without his consent and harm him and not inthe interest of public, etc. showed median score of 3. Disclosure to parents without consent in case of majorand breach of professional secrecy is professional misconduct of doctor showed median score less than 3.Conclusion: Intern doctors had little knowledge regarding disclosure to parents without consent in caseof major and breach of professional secrecy is professional misconduct of doctor. Intern doctors were notsure about Professional secrecy is implied term of contract between doctor and patient and patient can suethe doctor for damages if disclosure is done without his consent and harm him and not in the interest ofpublic. Knowledge and awareness regarding rest of the facts related to privacy and confidentiality of medicalpractice found to be satisfactorily among intern doctors.